2016
DOI: 10.48550/arxiv.1603.01429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunity, Improving and Retrieving the lost entanglement of accelerated qubit-qutrit system via local Filtering

N. Metwally

Abstract: The possibility of immunized and improving the entanglement of accelerated systems via local filtering is discussed. The maximum bounds of entanglement depend on the dimensions of the accelerated and the filtered subsystems. If the small dimensional subsystem is accelerated and the large dimensional subsystem is filtered, one can get a long-lived entanglement. Moreover, if the larger subsystem is accelerated, then by filtering any subsystem, the upper bounds of entanglement of the filtered state are larger the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Fig. (1a), displays the behavior of entanglement of the final state (8), where it is assumed that, the partners share initially a singlet state i.e., c 11 = c 22 = c 33 = 1 and we have set α…”
Section: Entanglementmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. (1a), displays the behavior of entanglement of the final state (8), where it is assumed that, the partners share initially a singlet state i.e., c 11 = c 22 = c 33 = 1 and we have set α…”
Section: Entanglementmentioning
confidence: 99%
“…al, [7]. The immunity and protecting the entanglement of accelerated qubit-qutrit system by using the local filtering technique is investigated by Metwally [8]. Recently, it has been shown that the local weak-reverse measurements,(WRM) can be used as a technique to protect and improve the correlation in qubit-qutrit systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to revealing hidden quantum correlation properties, local filtering operations have other applications. In [20], Metwally discussed the possibility of immunization and improved the entanglement of accelerated systems via local filtering operations. Mayank et al showed the enhancement of a distillable key rate for quantum key distribution by local filtering for several bound entangled states [21].…”
Section: Introductionmentioning
confidence: 99%